Phytochemical Screening and Antioxidant Activity of Selekop (Lepisanthes amoena) Fruit - Heriad Daud Salusu; Farida Ariani; Ernita Obeth; Mark Rayment; Edy Budiarso; Irawan Wijaya Kusuma; Enos Tangke Arung (AGRIVITA, Journal of Agricultural Science, 2017)
Selekop (Lepisanthes amoena (Hassk.) Leenh.) plant leaves are used by the Dayak tribe of East Kalimantan as traditional cosmetics. Selekop fruit is also edible, but not well known. This study was conducted to obtain the phytochemical content and antioxidant assay in flesh, seed and pericarp extracts from the fruit of Selekop. Phytochemical analysis was conducted on ethanol extract for identification of flavonoid, alkaloid, tannin, saponin, triterpenoid and steroid. The antioxidant activity was done by DPPH assay with ascorbic acid as positive control. The flesh contained flavonoid, saponin, and tannin; the seed contained flavonoid, alkaloid, saponin, triterpenoid, and tannin; and the pericarp contained flavonoid, alkaloid, saponin, triterpenoid, and tannin. Analysis of antioxidant activity revealed the following Inhibitory Concentration (IC50 values): 122.51 ppm of flesh, 63.30 ppm of seed, 53.21 ppm of pericarp and 3.06 ppm of ascorbic acid. Based on these results, the ethanol extract of the seed and the flesh had a phytochemical content and antioxidant activity which was better than the flesh extract from Selekop fuit.